ENTREPRENEUR KNOWLEDGE: THE CONCEPTUAL FRAMEWORK - Damelina Basauli Tambunan; Norashidah Binti Hashim (IPTPI Surakarta, 2016)
The aim of this research is to give the conceptual idea of needed knowledge forentrepreneurs in managing thebusiness. There are some different perspectives toward entrepreneur, some opinion state that the most importantthing for anentrepreneur is the ability to execute the business idea while other stated that the planning isimportant as well. A qualitative study has been conducted to identify the knowledge needed by entrepreneurs torun their business. This study conducted aliterature review to find out the needed knowledge for anentrepreneur.This study finds out, there are four dimensions of entrepreneur knowledge which are explicit knowledge(functional knowledge) and tacit knowledge (skill). These dimensions were identified by using various literature.